الدراسة البنيوية والضوئية والكهربائية لشرائح اكسيد القصدير المطعم بالنحاس - حمروني, نور الدين (جامعة الوادي University of Eloued, 2017)
حى الاهخ اًو خلال هزا انع مً بذساست كم ي انخصائص انب ىٍُ تٌ ،انكهشبائ تٍ وانضىئ تٍ لأغش تٍ أكس ذٍ 1)، ورنك إ طَلاقا ي كهىس ذٌ - ب سُب %( 16 (Cu) وان طًعى بان حُاط (SnO انقصذ شٌ ان قُ ( 2 خٌى حشس بٍ ان حًهىل عهى سكائض صجاج تٍ ححج دسجت حشاسة (CuCl وكهىس ذٌ ان حُاط( 2 (SnCl انقصذ شٌ( 2 480 ن ذًة 4 دقائق ورنك ي خلال حق تٍُ انشش بالإ حَلال انحشاسي . أظهش إ عَشاج الأشعت انس تٍٍُ أ C° .( لأغش تٍ أكس ذٍ انقصذ شٌ ان طًعى بان حُاط ب تٍُ يخعذد انخبهىس سباع انضوا اٌ وحأخز الإحجا انخفض هٍ ( 200 أبذث ان فُار تٌ انضىئ تٍ حضا ذٌا ي % 80.88 إنى % 88.33 ، أيا ان قًاويت انسطح تٍ فقذ شهذث اسحفاعا حخى 1977.410 )ع ذُ سَبت انخطع ىٍ % 8 . حخغ شٍ ق ىٍ انفاصم انطاق وفقا ن سُب انخطع ىٍ بان حُاط ن أٍخز انق ىٍIn this work ,we studied structural, electrical, and optical characterization of undoped tin oxide (SnO2) and cuivre (Cu) doped (SnO2) thin films , Which have been deposited from tin chloride (SnCl2) and cuivre chloride(CuCl2)onto glass substrates by spray pyrolysis technique .Samples were deposited for 4 minutes at the substrate temperature of 480C°.The doping concentration of (Cu) was varied from 1 to 16 wt (%) in solution.X-ray diffraction (XRD) has shown polycrystalline structure according to Tetragonal , Rutile (SnO2) structure with (200) as preferential orientation for cuivre (Cu) doped (SnO2) thin films. The optical transmittance of (SnO2:Cu) films in visible region increases from 76% to 90%.The sheet resistance (Rsh) varied from )672.951Ω) to )6255.460Ω) for Cu-doping in the range 0-8 wt (%).The optical band gap (Eg) increased from (4.09.5eV)to (4.61.0eV)with increasing of the concentration of cuivre (Cu) dopants.
مدكرة ماستر تخصص فيزياء
Keywords: المفتاحية:أكس ذٍ انقصذ شٌ ( 2 إ عَشاج الأشعت اانشش بالإ حَلال انحشاسي ، الأغش تٍ انشق قٍت ،ان حُاطنس تٍٍُ , انفاصم انطاق ,ً ان قًاويت انسطح; Tin oxide (SnO2), Spray pyrolysis, Thin films